Changes in breeding activity of Southeast Asian songbirds in response to the severity of the dry season - Gale, George A.; Angkaew, Rongrong; Khamcha, Daphawan (Frontiers in Conservation Science, 2024)
Droughts are expected to become more frequent and severe as the climate changes. Tropical songbirds likely reduce reproductive output during extreme droughts such as El Niño events in Southeast Asia as a tradeoff for reducing mortality risks. However, the timing of these rainfall responses and the extent of these reproductive costs are largely unknown in this region. Here we quantified how the amount and frequency of rainfall impacted nest initiation (first egg dates), and how the amount of rainfall may impact the duration of nesting in a given season (last expected fledging date). We tested these hypotheses on seven species of understory passerines in a secondary dry evergreen forest in northeastern Thailand. Using ten years of data (2014–2023) we examined the relationship between rainfall examining both total amounts occurring at key parts of the year (such as just prior to the breeding season) as well the number of “no-rain” days (rainfall gap) on (1) first egg dates and the (2) last expected fledging date of a given season. More severe dry seasons (longer time gaps in rainfall) caused longer delays in the start of egg laying and gap days tended to have a stronger effect than total rainfall. Lower breeding season rainfall resulted in later fledge dates for four species; lower rainfall amounts during the dry season resulted in later fledge dates for three species. There was no relationship between first egg dates and last expected fledging dates for any target species. Overall, it appears that droughts are likely shortening the breeding seasons of many tropical forest birds, but the reproductive costs are still difficult to estimate precisely. Further investigation is also recommended as to how rainfall is affecting nesting success particularly whether greater rainfall is regularly associated with earlier end of season fledging dates.